Gender matters: family background and upper secondary education in Finland - Hautala Helena; Kallio Johanna (Policy Press, 2025)
The intergenerational transmission of education and social position is a widely studied topic, but measurement of the significance of gender in this subject has received less attention. We study gender differences in the effect of parental disadvantage on the probability of a child completing upper secondary education in Finland. We use high-quality register data, collected by Statistics Finland. The data are clustered according to families that includes information on both children and their parents. The data consist of a 25 per cent sample of persons born in Finland between 1980 and 1986 (n=157,135). The data are analysed using sibling methods using random-effects linear probability models. The analyses are run separately for daughters and sons. With the exception of parental unemployment, all the indicators measuring disadvantaged parental background are significantly more strongly connected to the probability of sons than the probability of daughters completing upper secondary education. Father’s unemployment is a stronger predictor of the child’s probability of completing upper secondary education than unemployment of the mother. The mother’s educational level predicts a child’s probability of completing upper secondary education more strongly than the educational level of the father. Both mothers’ and fathers’ educational levels have a significantly stronger correlation with sons’ than daughters’ completion of upper secondary education. Equality of opportunity seems to be achieved better among girls than among boys. It might be the case, that the educational system, as one of the most important paths for achieving superior social status to one’s parents, does not treat girls and boys equally. Were this so, it would be especially important to pay more attention to boys’ school readiness and school wellbeing, especially in socioeconomically disadvantageous areas.